Eco-cybernetics Approach to Knowledge and Information Science Education in Iran - Ehsan Geraei (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2019)
Purpose: The purpost of this research is to provide a theoretical model for educational planning in the field of Knowledge and Information Science (KIS) in Iran. To do so, while addressing the concepts of ecology and cybernetics theories and combining them with each other, a new approach called “Eco-cybernetics Appraoch” is introduced and explained. Method: This research was conducted using the documentary-analytical method. To gather the required information, a literature review of the cybernetics' and ecology's concepts and of the studies carried out into the future of KIS education was conducted. Findings: Eco-cybernetics approach to KIS education, like biological ecosystems, concerns simultaneously the environmental factors and pillars of education. Eco-cybernetics approach studies the interactive relationships between the pillars of KIS education and its environment. This approach regards the future of KIS education as a function of the interaction between the pillars of KIS education and its einvironment as well as its feedback and feed-forward systems. Originality/value: The attitudes put forward about the future of KIS can be divided into four groups. The first group includes a pessimistic approach to the future and a belief in the extinction and destruction scenario. The second group distinguishes between the "Library Science" and the "Information Science" and other new titles. They have warned the library science community against the pure optimism about their high share in the future jobs of the information society. In fact, they are concerned with the challenge of library science in its traditional concept and information science and other similar disciplines in its modern sense. The third group maintains that the path to the future passes through the past and present. In order to survive, KIS must focus on the intradisciplinary and extradisciplinary factors. In fact, this perspective refers to the progression and survival in a steady manner without major changes. The fourth group believes in a favorable future for KIS. They see planning and designing an education system aimed at educating the future generation students as the key to achieve this desirable future. The present research, for the first time, has addressed the Eco-Cybernetics approaches to the analysis of KIS education planning in Iran and can serve as a basis for the KIS education.